The paradox of the autonomy of Afro-descendants in the Colombian Pacific - Perafán, Mireya Valencia (Sustainability in Debate, 2019)
Claudia Leal. Landscapes of Freedom ”“ Building a Postemancipation Society in the Rainforests of Western Colombia. Tucson: The University of Arizona Press. 2018. 336 p. ISBN ”“ 13: 978-0-8165-3674-0 (cloth). US55.00. Figures, maps, graphs, tables, bibliography and index.